Twins Research Australia: A New Paradigm for Driving Twin Research. (26th December 2019) - Murphy, Kate; Lam, Janine; Cutler, Tessa; Tyler, Jess; Calais-Ferreira, Lucas; Li, Shuai; Little, Callie; Ferreira, Paulo; Craig, Jeffrey M.; Scurrah, Katrina J.; Hopper, John L.
Abstract: Twins Research Australia (TRA) is a community of twins and researchers working on health research to benefit everyone, including twins. TRA leads multidisciplinary research through the application of twin and family study designs, with the aim of sustaining long-term twin research that, both now and in the future, gives back to the community. This article summarizes TRA's recent achievements and future directions, including new methodologies addressing causation, linkage to health, economic and educational administrative datasets and to geospatial data to provide insight into health and disease. We also explain how TRA's knowledge translation and exchange activities are key to communicating the impact of twin studies to twins and the wider community. Building researcher capability, providing registry resources and partnering with all key stakeholders, particularly the participants, are important for how TRA is advancing twin research to improve health outcomes for society. TRA provides researchers with open access to its vibrant volunteer membership of twins, higher order multiples (multiples) and families who are willing to consider participation in research. Established four decades ago, this resource facilitates and supports research across multiple stages and a breadth of health domains.